The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cctc.202101045
|View full text |Cite
|
Sign up to set email alerts
|

Ge‐Substituted Hierarchical Ferrierite for n‐Pentane Cracking to Light Olefins: Mechanistic Investigations via In‐situ DRIFTS Studies and DFT Calculations

Abstract: The development of heterogeneous catalysts for light olefin production via a catalytic cracking has been crucially important due to the high demand of related products in industrial applications. Herein, we report the structural analysis of a germanium-substituted hierarchical ferrierite zeolite obtained by one-pot synthesis. This is the first report on an investigation of the synergistic effect of hierarchical structures and the onepot Ge-substitution in a ferrierite framework on the catalytic cracking mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Moreover, the acid site density was also determined by NH 3 -TPD, as listed in Table 1. 33 Considering the NH 3 -TPD features, pristine FER exhibits the highest density of acid sites compared to the other and contains two predominant peaks assigned as weak and strong acid sites. However, after the growth of the SN1 phase at the exterior surface, the weak and strong acid density of the FER/ SN1 composite decreased significantly compared to that of the pristine FER, and it should be noted that the medium acid sites were detected at the shoulder peak at 250−400 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the acid site density was also determined by NH 3 -TPD, as listed in Table 1. 33 Considering the NH 3 -TPD features, pristine FER exhibits the highest density of acid sites compared to the other and contains two predominant peaks assigned as weak and strong acid sites. However, after the growth of the SN1 phase at the exterior surface, the weak and strong acid density of the FER/ SN1 composite decreased significantly compared to that of the pristine FER, and it should be noted that the medium acid sites were detected at the shoulder peak at 250−400 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Typically, the ammonia desorption in the NH 3 -TPD profile is distributed to three different regions at (i) 150–250 °C; (ii) 250–400 °C; and (iii) 400–700 °C, corresponding to weak, moderate, and strong acid sites, respectively. Moreover, the acid site density was also determined by NH 3 -TPD, as listed in Table …”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffraction (XRD) analysis revealed that the crystallinity of all of the prepared samples is identical to the pristine Hie-ZSM-5 (Figure S1). It should be noted that the absence of any observable Fe characteristics in all the synthesized samples, as well as the well-dispersed Fe species within the hierarchical ZSM-5 framework, is observed . Moreover, N 2 adsorption–desorption isotherms of the pristine Hie-ZSM-5, 1.2Fe-Hie-ZSM-5, and impregnated Fe on Hie-ZSM-5 (1.2Fe-Hie-ZSM-5-IMP) were characterized to provide crucial insights into the textural properties as depicted in Figure S2 and Table S1.…”
Section: Resultsmentioning
confidence: 99%